Kinerja Prototipe Papan Osilasi Pada Pompa Flap Tenaga Gelombang Untuk Pemanfaatan Mata Air Di Pantai Banyu Asri, Kota Singaraja - Bali - Juventus Welly Ginting; I Ketut Dharma Setiawan (JURNAL TEKNIK HIDRAULIK, 2018)
The supply of raw water is generally water available from several sources, which are available only on a river, lake, water wells and springs. The extraction can be done by drilling, damming water, and pumping. Management of the potential of raw water in an area is determined by geographical and geological conditions. One of the occurrences of springs found in coastal areas is influenced by marine and geological parameters which will further affect the method of capture, management, and utilization. This prototype of raw water supply has been installed in a location around the spring at Banyu Asri Beach, Singaraja City, Buleleng Regency, Bali Province in 2013. Data collection methodology is carried out by observing the wave data, pumping discharge and water salinity. These observations were made for two types of oscillation boards, namely using wood and fiber. From this technology, it is expected that the supply of a stable source of springs and the mineral content that is maintained even though the position of the spring is strongly influenced by the tide of the sea water which often inundates the discharge point of the spring. The spring at Banyu Asri Beach has been widely used by the community for drinking water and ritual worship. From the results of the performance of the prototype after being installed at the location of the spring, it has shown the ability to drain fresh water through pipelines towards the land, although the wave height that occurs in very small locations ranges from 0.10 to 0.30 cm and the discharge flow is up to 0.03 L / sec.